Development of titanium nitride thin film microheaters using laser micromachining. (March 2022) - Jithin, M.A.; Ganapathi, K.L.; Ambresh, M.; Nukala, Pavan; Udayashankar, N.K.; Mohan, S.
Abstract: In this paper, we report the fabrication and characterization of titanium nitride (TiN) thin-film-based microheaters. TiN thin films have been optimized on Si and SiO2 substrates for their optimum electrical resistivities by controlling the process parameters, including argon:nitrogen (Ar:N2 ) ratio in reactive pulsed DC magnetron sputter (PDCMS) deposition technique. An optical emission spectroscope (OES) was used for monitoring the plasma characteristics at various nitrogen flow rates. The microstructural and surface properties of the TiN films have been investigated and correlated with the electrical properties. It has been observed that the amount of nitrogen flux in the TiN plasma plays an essential role in the microstructural, surface, and electrical properties of the TiN thin films. Micro-heaters have been fabricated with TiN thin films with low electrical resistivity using laser engraving techniques instead of conventional lithographic and micromachining techniques. The TiN microheater has shown excellent performance. A temperature of 406 °C has been achieved by applying an input power of 8 W. This work paves the path for developing scalable and economic TiN microheaters using laser micromachining techniques. Highlights: Scalable and economic micromachining technique, laser engraving technique was employed to fabricate TiN microheaters as a replacement for conventional lithography or focused ion beam milling techniques. The process parameters, including Ar:N2 ratio in pulsed dc magnetron sputtering (PDCMS), are optimized to achieve low resistive TiN thin films essential for the fabrication of high-temperature microheaters. The variation in the electrical resistivity of TiN thin films with respect to the process parameters was understood by correlating with the structural and microstructural properties. A maximum temperature of 406 °C at 8 W input power has been achieved with the fabricated TiN microheater.